2021
DOI: 10.1515/pac-2020-1101
|View full text |Cite
|
Sign up to set email alerts
|

Well-defined polyindole–Au NPs nanobrush as a platform for electrochemical oxidation of ethanol

Abstract: Over the recent decades, conducting polymers have received great interest in many fields including microelectronics, energy conversion devices, and biosensing due to their unique properties like electrical conductivity, stability, and simple synthesis. Modification of conducting polymers with noble metals e.g. gold enhances their properties and opens new opportunities to also apply them in other fields like electrocatalysis. Here, we focus on the synthesis of hybrid material based on polyindole (PIN) nanobrush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Also, photo-assisted techniques can enhance the detection/removal of chemicals from the solution. Nevertheless, when it comes to the particular chemicals monitoring in the water, the voltammetry-based method is one of the most commonly used (Warczak et al 2021 ). However, depending on the chemistry of the electrode, experimental conditions and the chosen method, the detection limit of dye and its degradation (and photodegradation) products can be increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, photo-assisted techniques can enhance the detection/removal of chemicals from the solution. Nevertheless, when it comes to the particular chemicals monitoring in the water, the voltammetry-based method is one of the most commonly used (Warczak et al 2021 ). However, depending on the chemistry of the electrode, experimental conditions and the chosen method, the detection limit of dye and its degradation (and photodegradation) products can be increased.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the PIN-Au NP electrode improved sensing compared to the bare GC. The PIN-Au NP layer onto the GC electrode was prepared with the procedure described in Warczak et al ( 2021 ). The surface area for GC was 0.0314 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…It may be due to the influence of both benzene and pyrrole rings in the structure, which in turn induce the characteristics of poly(para phenylene) and PPy. 18,19 Continuous research on PIn showed that it is a viable candidate for usage in different applications, which include supercapacitors, 20 batteries, electrochromic devices, 21 sensors, 22 electrocatalysis, 23 anticorrosion, 24 and nonlinear optics. 25,26 Numerous studies on the methods for incorporating nanoparticles into polymeric matrix have been published, taking the polymer in solution or in melt form, like ex situ polymerization, in situ polymerization, melt mixing, solution mixing, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among these, PIn can be easily synthesized by the simple chemical oxidation method and is thermally stable with a moderate rate of degradation, high redox activity, and tunable conducting properties when compared to other CPs. It may be due to the influence of both benzene and pyrrole rings in the structure, which in turn induce the characteristics of poly­(para phenylene) and PPy. , Continuous research on PIn showed that it is a viable candidate for usage in different applications, which include supercapacitors, batteries, electrochromic devices, sensors, electrocatalysis, anticorrosion, and nonlinear optics. , …”
Section: Introductionmentioning
confidence: 99%